Brain-specific transcriptional regulator T-brain-1 controls brain wiring and neuronal activity in autism spectrum disorders - Huang, Tzyy-Nan; Hsueh, Yi-Ping (Frontiers in Neuroscience, 2015)
T-brain-1 (TBR1) is a brain-specific T-box transcription factor. In 1995, Tbr1 was first identified from a subtractive hybridization that compared mouse embryonic and adult telencephalons. Previous studies of Tbr1–/– mice have indicated critical roles for TBR1 in the development of the cerebral cortex, amygdala and olfactory bulb. Neuronal migration and axonal projection are two important developmental features controlled by TBR1. Recently, recurrent de novo disruptive mutations in the TBR1 gene have been found in patients with autism spectrum disorders (ASDs). Human genetic studies have identified TBR1 as a high-confidence risk factor for ASDs. Because only one allele of the TBR1 gene is mutated in these patients, Tbr1+/– mice serve as a good genetic mouse model to explore the mechanism by which de novo TBR1 mutation leads to ASDs. Although neuronal migration and axonal projection defects of cerebral cortex are the most prominent phenotypes in Tbr1–/– mice, these features are not found in Tbr1+/– mice. Instead, inter- and intra-amygdalar axonal projections and NMDAR expression and activity in amygdala are particularly susceptible to Tbr1 haploinsufficiency. The studies indicated that both abnormal brain wiring (abnormal amygdalar connections) and excitation/inhibition imbalance (NMDAR hypoactivity), two prominent models for ASD etiology, are present in Tbr1+/– mice. Moreover, calcium/calmodulin-dependent serine protein kinase (CASK) was found to interact with TBR1. The CASK-TBR1 complex had been shown to directly bind the promoter of the Grin2b gene, which is also known as Nmdar2b, and upregulate Grin2b expression. This molecular function of TBR1 provides an explanation for NMDAR hypoactivity in Tbr1+/– mice. In addition to Grin2b, cell adhesion molecules－including Ntng1, Cdh8 and Cntn2－are also regulated by TBR1 to control axonal projections of amygdala. Taken together, the studies of Tbr1 provide an integrated picture of ASD etiology at the cellular and circuit levels.